IMPLEMENTASI KETELADANAN K. H. AHMAD DAHLAN DALAM PEMBELAJARAN MENULIS ESAI PADA MAHASISWA PBSI FKIP UNPAS - Rustandi, Adi; Mulkhan, Abdul Munir; Zamah Sari (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2025)
Abstract This research was motivated by 2 (two) things, namely the decline in character education (exemplary) of PBSI FKIP Pasundan University students and students' difficulties in writing essays. So, the aim of this research is to re-build the foundation for character education for PBSI FKIP students at Pasundan University in the fifth semester through the example of K. H. Ahmad Dahlan in learning to write essays. The research method used is an experimental method in the form of a quasi experimental design (quasi experiment). The research design used was the matched-only pretest-posttest control group. The results of this study showed that the average score of the experimental class before using the Jigsaw type cooperative learning method, the pre-test score was 64, the quality score was B-, between 2.41 to 2.41. 2.70, and good category. After using the Jigsaw type cooperative learning method, we got a score of 86, a quality score of A-, between 3.41 to 3.41. 3.70, and very good category. Meanwhile for the control class, before using the conventional method, the pre-test score was 61, the quality score was B-, between 2.71 to 2.71. 3.00, and good category. After using the conventional method, we got a score of 70, a quality score of B, between 2.71 to 2.71. 3.00, and good category. Next, in the experimental class, refer to the results ttable = 2.045, it turns out that tcount > from ttable, namely 11.64 > 2.045. Meanwhile, in the control class, the result was ttable = 2.045, it turned out that tcount > ttable, namely 5.60 > 2.045. So, it can be concluded that learning to write essays in the experimental class which contains the example of K. H. Ahmad Dahlan using the Jigsaw type cooperative learning model is very significant, successful and more effective than using conventional methods in the control class. Keywords: exemplary and essay writing